Typology of Fala Kanci House As a North Maluku Traditional House - Harisun, Endah (University of Merdeka Malang, 2020)
The Indonesian people are very rich in tradition and culture. One of the traditions and culture that still exists today is a traditional house. This traditional house has the uniqueness and characteristics of each region. Buttoned traditional house (fala kanci) is a traditional North Maluku house spread throughout North Maluku. Button house has unique characteristics, namely building construction. With building construction using wood as a building structure starting from beams on foundation, columns and beams which all bound together using traditional wooden pegs and joints. In this modern era the existence of traditional houses is increasingly rarely found. This research it is hoped that it can open up the horizons of thought about the existence and uniqueness of traditional houses owned by the people of North Maluku in general and the people of Ternate in particular. The typology approach by comparing four traditional houses of fala kanci was chose from four different villages, so that it can be conclude about the characteristics of fala kanci traditional houses in Ternate. These characteristics are in the form of building facades, floor plans, walls, foundations and construction of fala kanci traditional houses. Fala Kanci is also an earthquake resistant building because of the uniqueness of its building frame.Â DOI:Â https://doi.org/10.26905/lw.v12i2.4005